Review on Experimental Study of HPC using Tertiary Blends of GGBS and Metakaoline: Effect of Metakaolin on Mechanical and Durability Properties of High Performance Concrete (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The project is to study of HPC using tertiary blends of GGBS and Metakaoline. Concrete is the most extensively used construction material in the world. The addition of mineral admixture in cement has suddenly increased along with the development of concrete industry, due to the consideration of cost saving, energy saving, environmental protection and conservation of resources. however environmental view both in terms of damage caused by the extraction of raw material and carbon dioxide emission during cement manufacture have brought pressures to reduce cement consumption by the use of supplementary materials. High Performance Concrete (HPC) is the latest development in concrete. It has become more popular these days and is being used in many prestigious projects. Mineral admixtures such as fly ash, rice husk ash, metakaolin, silica fume GGBS etc are more commonly used in the development of HPC mixes This study presents the effect of metakaolin (MK) on the mechanical and durability properties of high strength concrete for a constant waterbinder ratio.The characteristics like workability, compressive strength and flexural test , RCPT ,durability of M60 grade .HPC mixes idifferent percentages of metakaolin or GGBS by weight of cement along with some suitable super plasticizer.